Profitabilitas dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) - Riri Mayliza; Dini Sri Dahyana (Lembaga Yasin AlSys, 2025)
This study is motivated by the gap in understanding regarding the influence of profitability and company growth on firm value in Indonesia’s banking sector, particularly during the 2019–2023 period. The objective is to examine the effect of profitability and company growth on firm value among banks listed on the Indonesia Stock Exchange (Bursa Efek Indonesia or BEI). A quantitative approach was employed using multiple linear regression analysis based on panel data, obtained from the annual financial statements of 38 banking companies selected through purposive sampling. Data analysis was conducted using E-Views version 12 software and included model feasibility tests (Chow test, Hausman test, and Lagrange Multiplier test), normality test, and partial hypothesis testing using the t-test at a 5% significance level. The results indicate that profitability, measured by Return on Assets (ROA), has a positive and significant effect on firm value, while company growth does not show a significant effect. These findings confirm that profitability is a primary determinant of firm value as perceived by investors in the BEI banking sector. This research contributes meaningfully to corporate financial management and investment strategy in the banking industry and recommends that future studies expand the variables and sample scope to generate more comprehensive and applicable insights.